When common turns uncommon – an atypical presentation of childhood tuberculosis - Joshy, Akhil; Philip, Bincy; Cherian, Carol S.; Abraham, Jacob (International Journal of Contemporary Pediatrics, 2026)
Paediatric tuberculosis (TB) presents distinct challenges compared to adult TB in its diagnosis, clinical presentation, and management. Diagnosis in children is often difficult because symptoms are frequently non-specific or absent, and microbiological confirmation is hard to achieve. Young children are more likely to develop extrapulmonary or disseminated forms of TB than adults., lethargy, and significant weight loss (05 kg) without cough. Clinical examination revealed markedly reduced air entry on the left side. Laboratory investigations showed elevated inflammatory Management is complicated by the lack of paediatric drug formulations and the need for careful monitoring of potential drug toxicity. Despite these challenges, children generally tolerate anti-tubercular therapy well, and treatment regimens are largely similar to those used in adults. We report a child with large mediastinal mass who was proven to have extra pulmonary tuberculosis. This case emphasizes the atypical presentation of paediatric TB as a mediastinal cystic lesion, mimicking other pathologies. It highlights the need for maintaining a high index of suspicion, especially when initial microbiological tests are negative, and underscores the importance of obtaining tissue diagnosis in suspected extrapulmonary TB. Early recognition and appropriate management are essential to prevent complications and ensure favourable outcomes in paediatric tuberculosis.